Polímeros ionoméricos e sua aplicação em supercapacitores: potencialidades e limitações - Sampaio, Artur Ribeiuro (Universidade Federal de São Carlos, 2023)
The following work addresses the importance of studying ionomeric polymers and supercapacitors. These polymers are materials that contain ions in their structure, providing unique and interesting properties such as high ionic conductivity combined with mechanical and thermal stability. They have been widely used in electrochemical energy applications, including fuel cells, electrocatalysis, and rechargeable batteries, while also playing a significant role in the pursuit of sustainable solutions through their application in clean and sustainable energy technologies. Supercapacitors, on the other hand, are devices responsible for storing a high energy density compared to conventional batteries. They are capable of releasing this high energy density rapidly, making them highly suitable for various applications such as electric vehicles, portable electronics, and energy storage systems. Supercapacitors also exhibit a prolonged lifespan, enduring numerous charge and discharge cycles without significant performance degradation. Delving deeper into the study of these materials and technologies enables advancements in the development of sustainable, efficient, and economically viable energy storage solutions. Consequently, it contributes to the transition towards renewable energy sources and the reduction of carbon emissions. Therefore, exploring the properties and applications of these materials is of paramount importance in driving innovation and addressing current energy and environmental challenges.
Iomeric polymers and their application in supercapacitors: potentials and limitations
Keywords: Polímeros ionoméricos; Supercapacitores; Energia eletroquímica; Armazenamento de energia; Condutividade iônica; Sustentabilidade; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS